Fetal fibronectin test for threatened preterm delivery 48h after admission: Cost-effectiveness study. (March 2019) - Mourgues, Charline; Rossi, Amélie; Favre, Nathalie; Delabaere, Amélie; Roszyk, Laurence; Sapin, Vincent; Debost-Legrand, Anne; Gallot, Denis
Abstract: Objective: The aim of this work was to assess the cost-effectiveness of the fetal fibronectin (fFN) test at 48 h after admission for threatened preterm delivery to promote early discharge. Study design: Before-and-after study to calculate the incremental cost-effectiveness ratio (ICER). Patients were enrolled 48 h after admission in a tertiary care centre for threatened preterm delivery between 24 +0 and 34 +6 weeks. fFN testing was performed. During the first period, physician was blinded to fFN test and discharge occurred after apparent reduced symptomatology at physician's discretion. During the second period, fFN test was revealed to physician and discharge was immediately proposed to negative test patients. The costs considered in this analysis were the direct medical costs from the hospital perspective: costs of hospitalisation, treatment, and imaging procedures. The efficacy criterion selected was the number of deliveries at 7 and at 14 days after admission for threatened preterm delivery. Results: The study included 178 pregnant patient, 99 during the first period (July 2008-October 2009) and 79 during the second (March 2010-February 2012). The lengths of hospital stays were shorter during the second period, with more than 50% of women discharged home between 48 and 72 h (p < 0.0001) resulting in a cost-saving of 76 051 euros. The number of deliveries at 7 and at 14 days was similar between the two periods. Conclusion: The fFN test at 48 h after admission supported early discharge and was safe and cost-effective.